Primeiro registro de Aedes albopictus no Estado de Santa Catarina, Brasil First report of Aedes albopictus in the state of Santa Catarina, Brazil - Peter Löwenberg-Neto; Mário A Navarro-Silva (Universidade de São Paulo, 2002)
Três fêmeas adultas de Aedes (Stegomyia) albopictus (Skuse) foram capturadas por meio de isca humana em área peridomiciliar de remanescente de Mata Atlântica na Praia de Itaguaçu, Ilha de São Francisco do Sul, litoral Norte de Santa Catarina. Three adult females of Aedes (Stegomyia) albopictus (Skuse) were captured using a human bait in the surrounding dwelling area of the remaining rain forest in Itaguassu beach, island of São Francisco do Sul, northern coast of the state of Santa Catarina, Brazil.